Perencanaan Peningkatan Kualitas dengan Menggunakan Integrasi Metode Six Sigma dan ISO 9001:2000 - Imron Kuswandi (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
Companies who produce several of cigarettes, one of the kinds is BM Universal 12. To produce product with best quality and due to give satisfaction toward its consumer, there are several problem faced by the cigarette production process which is there are still defect product in its production process. From this condition, they need one method to deal with the matter. Using six sigma methods, they can identify defect product and by doing that they could improve the quality of the product. In this experiment it's using integration method by combining six sigma method and ISO 9001:2000. Six sigma methods is expected to be able minimizing the defect in PT